ANALISIS PELAYANAN BPJS DI INDONESIA DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DENGAN PENDEKATAN PROBLEM TREE ANALYSIS - Sukardi, Salsa Izza Shafinaz; Fadilla, Anisa Nur; Al Amin, Muhammad Noer Falaq (Jurnal Pahlawan, 2024)
This research aims to identify problems in BPJS services in Indonesia in improving community welfare using a problem tree analysis approach. The problem tree analysis method is used in this research to identify the root of problems in BPJS services, to provide a clearer picture, more appropriate solutions, good treatment priorities, as well as a structured evaluation and improvement process for BPJS services in the future. The research results revealed several main problems in BPJS services, such as low service quality, lack of service management, employee discriminatory behavior, and limited facilities and infrastructure. These problems violate the principles of good governance, such as the supremacy of law, effectiveness, efficiency, equality, accountability, and transparency. This condition makes it difficult for people to access quality and timely health services and can have a serious impact on people's health and welfare. This research suggests the need to increase supervision, optimize coordination, train employees, distribute facilities and infrastructure, and implement a reward and punishment system to improve the quality of BPJS services. With planned improvement efforts, it is hoped that BPJS Health services can provide optimal benefits for the health and welfare of the Indonesian people as a whole.   Keywords: Service, BPJS, Good Governance, Problem Tree Analysis